Perancangan Sistem Informasi Retensi Rekam Medis Menggunakan Metode Waterfall - Etika Sustiana (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
The implementation of hospital retention is carried out in accordance with SOP (Standard Operational Procedure) to help expedite the retention process. The aim of this research is to develop a medical record retention information system to identify problems faced by hospitals and how to overcome these retention problems. Data collection techniques were carried out by means of observation and interviews, as well as an information system developed using the waterfall method. From this study found several problems in the retention system that is still using a manual system, not yet fully computerized. Files are sorted individually, there is no retention schedule, there is no storage space available to separate active and inactive medical records. Therefore, a medical record retention information system was designed in the form of an application. The methodology used is flowcharts, context diagrams, data flow diagrams, and entity relationship diagrams, and is implemented using Microsoft Visual Studio 2010 and Microsoft Access as DBMS (Database Management System). Thus, it can be concluded that the system will make it easier for officers to carry out extermination effectively and precisely.